Конструктивні особливості автобусів великого класу та симуяційні моделі їх руху у середовищі SIMULINK - Кіндрацький, Богдан; Войтків, Станіслав; Осмак, Олексій (Видавництво Львівської політехніки, 2018)
General information about high-class buses, its advantages and drawbacks, development prospects are considered. Simulation model of a multi-axle bus in MATLAB Simulink software environment is presented.
Design features of high class busses and simulation models of its riding at SIMILINK software
Keywords: 629.022